(untitled) (Global Journal of Medical Research, 2024)
In this study the clinical records of canine patients seen at the Pet a Vet veterinary clinic in Guatemala between 2018 and 2020 were analyzed with the aim of investigating heart disease in dogs in the region From a total of 1215 records reviewed 825 cases of heart disease were identified with chronic mitral valve disease being the most frequent A higher incidence was observed in males and in Schnauzer breed dogs In addition the majority of diagnosed patients were found to be 9 years of age or older These results provide valuable information on the epidemiology of canine heart disease in Guatemala which may be useful to improve its diagnosis and clinical management